The effects of collective anger and fear on policy support in response to terrorist attacks. Issue 5 (2nd September 2016) - Kim, Jaeshin
ABSTRACT: Both correlational and experimental studies examined how perceived emotional responses of the majority of Americans to 9/11 affect individuals' support for government counter-terrorism policies (i.e., military intervention, anti-immigration, restricting civil liberties). Study 1 found associations between perceived collective emotions (i.e., anger, fear) and individuals' own corresponding emotions and those between perceived collective anger and counter-terrorism policy support. Individuals' own anger mediated the associations of collective anger with policy support. Using experimental manipulations, Study 2 showed that collective anger had a significant effect on individuals' own anger and one significant and two marginal effects on counter-terrorism policy support. Individuals' own anger mediated one of the marginal effects of collective anger on policy support. Implications of these findings are discussed in the context of terrorist threat.